With and without warning: managing ecosystems in a changing world. Issue 9 (1st November 2015) - Pace, Michael L; Carpenter, Stephen R; Cole, Jonathan J
Abstract : Many ecosystems are likely to experience abrupt changes and extreme conditions due to forces such as climate change. These events and their consequences – including the loss of ecosystem services – may be predictable or may occur without warning. Given these considerations, greater efforts are needed in two areas of research: improvements in early warning capability and advances in the management of ecosystems to enhance resilience. Current research has provided enhanced forecasting ability, scenario analysis, and detection of statistical anomalies that indicate abrupt change, but two key concerns remain: the detection of early warning signs near thresholds of change and the use of such warnings for ecosystem management. Furthermore, there may be no advance warning for some types of abrupt change, reinforcing the need to enhance resilience by managing ecosystems to reduce the possibility of crossing thresholds of change. Designing and implementing large‐scale management programs is one way to confront these problems.